2015
DOI: 10.1136/jmedgenet-2015-103104
|View full text |Cite
|
Sign up to set email alerts
|

Mutations inSLC1A4, encoding the brain serine transporter, are associated with developmental delay, microcephaly and hypomyelination

Abstract: The clinical phenotype of ASCT1 deficiency is reminiscent of defects in L-serine biosynthesis. The data underscore that ASCT1 is essential in brain serine transport. The SLC1A4 p.E256K mutation has a carrier frequency of 0.7% in the Ashkenazi-Jewish population and should be added to the carrier screening panel in this community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 13 publications
6
73
0
Order By: Relevance
“…Utilizing the power of our large data set, we were able to identify novel candidate genes in which multiple patients with similar phenotypes had rare variants predicted to result in loss of function, many of which were de novo. Access to this large number of cases has proven extremely valu- [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] As a result of our experience, we believe that candidate genes should be reported from WES analysis and shared in databases, such as GeneMatcher, so that clinicians, researchers, and clinical laboratories can be connected to facilitate more rapid dissemination of information and validation of novel disease genes. Our series is larger than previously reported clinical diagnostic series and has the power to begin to address the yield of WES for a large number of clinical indications.…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing the power of our large data set, we were able to identify novel candidate genes in which multiple patients with similar phenotypes had rare variants predicted to result in loss of function, many of which were de novo. Access to this large number of cases has proven extremely valu- [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] As a result of our experience, we believe that candidate genes should be reported from WES analysis and shared in databases, such as GeneMatcher, so that clinicians, researchers, and clinical laboratories can be connected to facilitate more rapid dissemination of information and validation of novel disease genes. Our series is larger than previously reported clinical diagnostic series and has the power to begin to address the yield of WES for a large number of clinical indications.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that other transporters are responsible for the extrusion of serine from the astroglial cells into the CSF; therefore, CSF serine level remains normal despite the defective ASCT1 transporter [3]. All previously reported children with serine transport defect were diagnosed through whole exome sequencing which identified biallelic mutations in the SLC1A4 gene encoding the ASCT1.…”
Section: Clinical Biochemical and Molecular Aspects Of Serine Transmentioning
confidence: 98%
“…Serine transport defect resulting from deficiency of the ASCT1, the main transporter for serine in the central nervous system, has been recently described in children with neurological manifestations that overlap with those observed in serine biosynthesis defects (Table 1) [4,3,5].…”
Section: Clinical Biochemical and Molecular Aspects Of Serine Transmentioning
confidence: 98%
See 2 more Smart Citations